(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3cJGH GdWGA HGH GdWGA heG HYOgeG ef GdMQha ai GdeVGYa s
(3BNQgG (B:s
(3hjMhR EKHGJ GdCda hGdgGA hGdhba Je GdQHY GdQGHY ef cJGH TeS GdYdhe HMeO Gddg GdhGMO GdMi Gdbjhe hHJeGeg Je GdcJGH s
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1061s
Keywords: (3GddZIs